Anisotropically elasto-plastic solution to undrained cylindrical cavity expansion in K0-consolidated clay. (March 2016) - Li, Lin; Li, Jingpei; Sun, De'an
Abstract: This paper presents an anisotropically elasto-plastic solution to the undrained expansion of a cylindrical cavity in K 0 -consolidated clay. The elasto-plastic constitutive relationship following the soil yielding process is described by the K 0 -based modified Cam-clay ( K 0 -MCC) model, which can properly reflect the anisotropic effects on the soil behaviour. Following the large strain deformation theory, the problem is reduced to solving a system of first-order ordinary differential equations in the plastic region. The semi-analytical solutions to the radial, tangential and vertical effective stresses are obtained using the Lagrangian method and the elastic–plastic (EP) boundary conditions. In addition, based on the semi-analytical results, an approximate closed-form solution is presented for practical purposes. Extensive comparisons with the isotropic constitutive model-based solutions have been performed to illustrate the effects of the initial stress anisotropy and initial stress-induced anisotropy on the cavity expansion and the stress distributions. The present solution incorporates the anisotropic properties of the natural K 0 -consolidated clay, thereby providing a more realistic theoretical basis for the practical engineering problems such as the pile installation and the pressuremeter tests.